1999
DOI: 10.1046/j.1523-1747.1999.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectra of Basal Cell Carcinomas are Distinct from Non-Tumor-Bearing Skin Components

Abstract: Infrared spectroscopy, by probing the molecular vibration of chemical bonds, directly indicates tissue biochemistry. An expanding body of literature suggests that infrared spectra distinguish diseased from normal tissue. The authors used infrared spectroscopy to examine basal cell carcinoma to explore distinctive characteristics of basal cell carcinoma versus normal skin samples and other skin neoplasms. Spectra of epidermis, tumor, follicle sheath, and dermis were acquired from unstained frozen sections, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(89 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…[79][80][81] By noninvasive methods, in-vivo NIR spectroscopy can be used to map the extent of BCCs and also to distinguish them from other cutaneous tumors with a high degree of accuracy. [79][80][81][82][83] That the two proposed mechanisms of tumorigenesis are complementary is suggested by the fact that shh-expressing cells also manifest increased expression of bcl-2, 84 likely through activation of the Gli proteins that are expressed in the outer root sheath of the normal hair follicle and in BCCs; 65 Gli-2 in particular appears to play an important role in the activation of the BCL2 gene. 70 …”
Section: Sporadic Bccmentioning
confidence: 99%
“…[79][80][81] By noninvasive methods, in-vivo NIR spectroscopy can be used to map the extent of BCCs and also to distinguish them from other cutaneous tumors with a high degree of accuracy. [79][80][81][82][83] That the two proposed mechanisms of tumorigenesis are complementary is suggested by the fact that shh-expressing cells also manifest increased expression of bcl-2, 84 likely through activation of the Gli proteins that are expressed in the outer root sheath of the normal hair follicle and in BCCs; 65 Gli-2 in particular appears to play an important role in the activation of the BCL2 gene. 70 …”
Section: Sporadic Bccmentioning
confidence: 99%
“…Recently, quantitative diagnosis based solely on the spectral information of tissue with simultaneous sensitivity and specificity higher than 90% was demonstrated for many cancer types, including skin (11)(12)(13)(14)(15), esophagus (16), prostate (17)(18)(19)(20)(21), breast (22), and lung (23, 24) (here, sensitivity represents the percentage of correctly detected tumor samples relative to the total number of tumor samples, and specificity is the percentage of correctly identified nontumor samples relative to the total number of nontumor samples). Nevertheless, achieving objective diagnosis while maintaining a high spatial resolution (20-50 ÎŒm) required tissue sectioning and long data acquisition times: typically 30-40 min/mm 2 for infrared microscopy and 5-20 h/mm 2 for Raman microscopy (13,15,20,23,25).…”
mentioning
confidence: 99%
“…A similar study using Fourier-transformed infrared (FT-IR) spectroscopy of mdx muscles was able to follow the progression of fibrosis (collagen content and accumulation) during dystrophy, and also traced the partial alleviation of collagen accumulation after treatment with steroids (Shaw et al, 1996). These studies from the muscle literature, illustrate how a correlation of measures taken independently from different approaches can extend the impact of the conclusions that are reached, and similar combination studies of cancer diagnostics, screening, prognostic and treatment outcome have been shown highly advantageous (McIntosh et al, 1999;Kirkham et al, in press;Shah et al, 2006;Delorme and Weber, 2006;Weber et al, 2006;Huzjan et al, 2005).…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 77%